Climatic Signals from Intra-annual Density Fluctuation Frequency in Mediterranean Pines at a Regional Scale - Zalloni, Enrica; de Luis, Martin; Campelo, Filipe; Novak, Klemen; De Micco, Veronica; Di Filippo, Alfredo; Vieira, Joana; Nabais, Cristina; Rozas, Vicente; Battipaglia, Giovanna (Frontiers in Plant Science, 2016)
Tree rings provide information about the climatic conditions during the growing season by recording them in different anatomical features, such as Intra-Annual Density Fluctuations (IADFs). IADFs are intra-annual changes of wood density appearing as latewood-like cells within earlywood, or earlywood-like cells within latewood. The occurrence of IADFs is dependent on the age and size of the tree, and it is triggered by climatic drivers. The variations of IADF frequency of different species and their dependence on climate across a wide geographical range have still to be explored. The objective of this study is to investigate the effect of age, tree-ring width and climate on IADF formation and frequency at a regional scale across the Mediterranean Basin in Pinus halepensis Mill., Pinus pinaster Ait. and Pinus pinea L. The analyzed tree-ring network was composed of P. pinea trees growing at 11 sites (2 in Italy, 4 in Spain and 4 in Portugal), P. pinaster from 19 sites (2 in Italy, 13 in Spain and 4 in Portugal), and P. halepensis from 38 sites in Spain. The correlations between IADF frequency and monthly minimum, mean and maximum temperatures, as well as between IADF frequency and total precipitation, were analyzed. A significant negative relationship between IADF frequency and tree-ring age was found for the three Mediterranean pines. Moreover, IADFs were more frequent in wider rings than in narrower ones, although the widest rings showed a reduced IADF frequency. Wet conditions during late summer/early autumn triggered the formation of IADFs in the three species. Our results suggest the existence of a common climatic driver for the formation of IADFs in Mediterranean pines, highlighting the potential use of IADF frequency as a proxy for climate reconstructions with geographical resolution.